Neutrophil to lymphocyte ratio in parkinson’s disease: a systematic review and meta-analysis - Samaneh Hosseini; N Shafiabadi; Monireh Khanzadeh; Arshin Ghaedi; Raziyeh Ghorbanzadeh; Amir Azarhomayoun; Aida Bazrgar; Jalil Pezeshki; Hanieh Bazrafshan; Shokoufeh Khanzadeh (2023)
Abstract Background The goal of this research was to explore the role of Neutrophil to lymphocyte ratio (NLR) in Parkinson’s disease (PD). Methods From inception to 4 June 2023, PubMed, Web of Science, and ProQuest were searched for papers comparing NLR in PD to healthy individuals. Standardized mean difference (SMD) with a confidence interval (CI) of 95% were calculated. Results A random-effect model revealed that PD patients had elevated NLR values compared to healthy individuals (SMD = 0.81, 95% CI = 0.47 to 1.14, P < 0.001). The results of subgroup analysis were as follows: (1) study design: We observed that patients with PD had higher levels of NLR than healthy controls in either retrospective (SMD = 1.12, 95% CI = 0.58 to 1.66, P < 0.001) or prospective (SMD = 0.43, 95% CI = 0.18 to 0.68, P = 0.001) studies. (2) Ethnicity: We noticed that individuals with PD had higher levels of NLR than healthy controls, whether they were East Asian (SMD = 0.93, 95% CI = 0.22 to 1.63, P = 0.010) or Caucasian (SMD = 0.75, 95% CI = 0.40 to 1.10, P < 0.001).The pooled sensitivity of NLR in the prediction of PD was 0.67 (95% CI = 0.61–0.73), and the pooled specificity was 0.66 (95% CI, 0.61–0.70). Conclusions Increased levels of NLR is highly related with the presence of PD. Further research is needed to determine the potential clinical benefits of this simple and low-cost biomarker in the PD diagnosis.